Testicular cancer: improving outcomes with national quality performance indicators. Issue 1 (24th March 2020) - Baxter, Mark A; MacDonald, Graham; Malik, Jahangeer; Law, Alistair; Dahle-Smith, Åsa; Mmeka, Walter; Donat, Roland; Shukla, Cj; Connor, John; Houston, Colin; Waterston, Ashita; White, Jeff
Abstract : Testicular cancer is the most common malignancy in young adult men. The prognosis is excellent in limited disease and cure is possible even in advanced disease. Quality performance indicators (QPI) are used in many developed countries as a measure of healthcare performance. We report and discuss the development of a national set of QPIs in Scotland for testicular cancer as a method of gathering demographic data and driving improvement in nationwide testicular cancer outcomes.